SUBSTANTIATION OF USE OF NANOPREPARATION IN COMPLEX TREATMENT OF PATIENTS WITH CHRONIC GENERALIZED PERIODONTITIS OF I-II DEGREE - Dubyna, V.A.; Skrypnykov, P.N.; Хавалкіна, Л.М.; Коробейнікова, Ю.Л.; Korobeinikova, Yu.L. (World of Medicine and Biology, 2019)
Currently, periodontal disease is rating first among dental diseases. Among all known treatment methods, in complex therapy the leading one is local therapeutic treatment with various preparations, the choice of which should be based on the degree and form of the pathology and severity of the course of chronic generalized periodontitis (CGP). In our study we used nanopreparation called Fullerene-C60. Good tolerability and safety of the preparation in treatment of CGP allows us to consider it as a non-injectable alternative to conventional methods of treatment. The nanopreparation was used in the irrigator and in the form of instillations / applications (or their combination) in each periodontal pocket. The area of protein fractals before and after administration of Fullerene-C60 has been studied. The findings of the study showed that the protein fractal area in two groups decreased on the average by 2.480%. The use of Fullerene-C60 in the form of irrigation and instillation / applications showed a clear decrease in the area of protein fractals in tiziographic samples, which proves the rational use of this nanopreparation.
Keywords: Fullerene-C60 nanopreparation; periodontitis; biofilm